2020
DOI: 10.1371/journal.pntd.0008544
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, etiological and epidemiological investigations of hand, foot and mouth disease in southern Vietnam during 2015 – 2018

Abstract: Hand, foot and mouth disease (HFMD) continues to challenge Asia with pandemic potential. In Vietnam, there have been two major outbreaks occurring during 2011–2012 (>200,000 hospitalizations and >200 deaths) and more recently in 2018 (>130,000 hospitalizations and 17 deaths). Given the high burden and the complex epidemic dynamics of HFMD, synthesizing its clinical and epidemiological data remains essential to inform the development of appropriate interventions and design public health measures. We report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…320/322 CVA16 patients with available demographic and clinical information were included for analysis in the present study. Most (59.4%) of these patients were male, in agreement with previous reports ( Le et al, 2020 ; Min et al, 2021 ). The median age was 20.82 months.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…320/322 CVA16 patients with available demographic and clinical information were included for analysis in the present study. Most (59.4%) of these patients were male, in agreement with previous reports ( Le et al, 2020 ; Min et al, 2021 ). The median age was 20.82 months.…”
Section: Resultssupporting
confidence: 93%
“…We showed that together with EV-A17, CVA10, and CVA6, CVA16 is one of the most predominant HFMD pathogens associated with severe clinical phenotypes in Vietnam during the study period (2011–2017). Of these, EV-A71 was the leading cause ( Van Hoang et al, 2019a ; Le et al, 2020 ). Additionally, despite its relatively stable genetic diversity, CVA16 dispersed widely between HCMC and other neighboring provinces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations